2022
DOI: 10.3390/cancers14215178
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Propionibacterium acnes Promotes Ovarian Cancer Progression via Regulating Hedgehog Signalling Pathway

Abstract: Background: The oncogenesis and progression of epithelial ovarian cancer (EOC) is a complicated process involving several key molecules and factors, yet whether microbiota are present in EOC, and their role in the development of EOC, remains greatly unknown. Methods: In this study, 30 patients were enrolled to compare the similarities and differences of intratumour microbiota among patients with epithelial benign ovarian tumours (EBOTs) and patients with EOC based on the high-throughput sequencing method. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It is believed that these changes could be linked to the severity of Cervical Intraepithelial Neoplasia (CIN), with an increase in Bacillus and Anaerococcus and a decrease in Gardnerella vaginalis potentially indicating a greater severity of the condition [ 36 ]. There are some studies suggesting that Propionibacterium acnes contributes to the development of several diseases in the prostate [ 37 ], gastric cancer [ 38 ], and ovarian cancer via regulating the hedgehog signaling pathway [ 32 ]. In this study, it was suggested that the genus level of Propionibacterium may be responsible for converting the cyst fluid environment to an environment with a lower concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that these changes could be linked to the severity of Cervical Intraepithelial Neoplasia (CIN), with an increase in Bacillus and Anaerococcus and a decrease in Gardnerella vaginalis potentially indicating a greater severity of the condition [ 36 ]. There are some studies suggesting that Propionibacterium acnes contributes to the development of several diseases in the prostate [ 37 ], gastric cancer [ 38 ], and ovarian cancer via regulating the hedgehog signaling pathway [ 32 ]. In this study, it was suggested that the genus level of Propionibacterium may be responsible for converting the cyst fluid environment to an environment with a lower concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intratumoral Propionibacterium acnes found in ovarian cancer tissue seems to play a key role in cancer progression by aberrant hedgehog signaling activation [111]. In vitro studies have demonstrated that the original bacterial molecule, such as lipopolysaccharide Escherichia coli, can induce the release of pro-inflammatory cytokines in ovarian cancer cells, promoting tumor growth and chemo-resistance through the stimulation of TLR (toll-like receptor) receptors [112].…”
Section: Endocrine Factorsmentioning
confidence: 99%
“…The study discovered that the P . acnes strain had a significant impact on the development of EOC [ 84 ].…”
Section: Vaginal Microbiota In Gynecological Cancersmentioning
confidence: 99%